Genomic potential and physiological characteristics of C1 metabolism in novel acetogenic bacteria - Yu, Jihyun; Park, Mi-Jeong; Lee, Joungmin; Kwon, Soo Jae; Lim, Jae Kyu; Lee, Hyun Sook; Kang, Sung Gyun; Lee, Jung-Hyun; Kwon, Kae Kyoung; Kim, Yun Jae (Frontiers in Microbiology, 2023)
Acetogenic bacteria can utilize C1 compounds, such as carbon monoxide (CO), formate, and methanol, via the Wood-Ljungdahl pathway (WLP) to produce biofuels and biochemicals. Two novel acetogenic bacteria of the family Eubacteriaceae ES2 and ES3 were isolated from Eulsukdo, a delta island in South Korea. We conducted whole genome sequencing of the ES strains and comparative genome analysis on the core clusters of WLP with Acetobacterium woodii DSM1030 T and Eubacterium limosum ATCC8486 T . The methyl-branch cluster included a formate transporter and duplicates or triplicates copies of the fhs gene, which encodes formyl-tetrahydrofolate synthetase. The formate dehydrogenase cluster did not include the hydrogenase gene, which might be replaced by a functional complex with a separate electron bifurcating hydrogenase (hydABCDE). Additionally, duplicated copies of the acsB gene, encoding acetyl-CoA synthase, are located within or close to the carbonyl-branch cluster.The serum bottle culture showed that ES strains can utilize a diverse range of C1 compounds, including CO, formate, and methanol, as well as CO2. Notably, ES2 exhibited remarkable resistance to high concentrations of C1 substrates, such as 100% CO (200 kPa), 700 mM 2 formate, and 500 mM methanol. Moreover, ES2 demonstrated remarkable growth rates under 50% CO (0.45 h -1 ) and 200 mM formate (0.34 h -1 ). These growth rates are comparable to or surpassing those previously reported in other acetogenic bacteria. Our study introduces novel acetogenic ES strains and describes their genetic and physiological characteristics, which can be utilized in C1-based biomanufacturing.